DEVELOPING TALENT POTENTIAL FOR A DYNAMIC BUSINESS ENVIRONMENT: A CASE OF THREE ZAMBIAN PUBLIC INSTITUTION EMPLOYEES - Mbewe, Serah (Advances in Social Sciences Research Journal, 2019)
As institutions plan for survival in an ever-changing business environment, they need to have employees that can not only perform exceptionally but also develop into future leaders called talent potentials. Therefore, the institution needs to assess the required talent potential according to its current and future strategic needs. The results of the assessment should guide the search, recruitment, and selection for the required talent potential. Once the institution has acquired this talent, the institution should retain it and develop it at all the different levels. This paper explores the talent management cycle from assessment to management of the talent with the institution with the hope of managing talent potential through the assessment of three specific individuals from three different business environments in the Zambian public sector. It also draws to the attention of how nature and future needs of the specific institution affects the specific strategic talent potential that the institution would require in order to adapt in an ever-changing business environment